(untitled) (Journal of Comparative & International Higher Education, 2024)
The Bologna Process is a mature and established topic, which makes it hard for early-career researchers to bring new perspectives on the process. Furthermore, there is a problem studying the Bologna process in non-EU countries as Bologna emerged as outside the framework of the European integration. Employing the concept of localization by Amitav Acharya, the paper examines factors driving the adoption of the Bologna process or its elements in the post-Soviet context. Furthermore, the paper examines factors driving the process of localization of the Bologna process in Kazakhstan. The present literature review suggests a novel and useful perspective that stresses the role of norm-takers in the Bologna process in non-EU countries. Stressing the role of the local factors, the paper aims to show why the convergence to the Bologna model is not likely to occur in Kazakhstan. The article contributes to the convergence-divergence debate in higher education.